The Experiences of Women Transitioning from Unhoused to Housed in High-Income Countries: A Systematic Review and Meta-Aggregation - Ghazaleh Salahi; Nadine Wathen; Abe Oudshoorn; Erin Dej; Carrie Anne Marshall (International Journal on Homelessness)
There are pathways in and out of homelessness that are gender-specific. However, little is known about the range of existing studies on the experiences of women who recently transitioned from homeless to housed in high-income countries. To date, no systematic reviews have brought together qualitative analyses from studies exploring women’s experiences who are re-housed in high-income countries. To fill this gap in existing literature, we performed a systematic review, utilizing the methods described by the Joanna Briggs Institute (JBI) (Lockwood et al., 2020) and Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines (Moher et al., 2010) to understand the meaning and experience of women exiting homelessness in high-income countries. We combined the search terms related to women, homelessness, and housing transitions and deployed them in six databases. Our research yielded 3025 titles and abstracts following the removal of duplicates. After conducting a title and abstract screening, 91 full-text articles remained. 14 articles were deemed to meet pre-established inclusion criteria. Our meta-aggregation revealed four themes generated through our analysis: a) ongoing presence of trauma in women’s lives; b) healing through providing support to others; c) lack of control over circumstances that enable survival; and d) support in housing decreases marginalization. This review deepens knowledge of the current research priorities as well as practical policy and practice strategies that can be utilized to support recently rehoused women to prevent recurrent periods of homelessness and its devastating impacts.